Pemberdayaan Kelompok Petani Kopi Cipta Lestari dalam Pengelolaan Limbah Kopi yang Berkelanjutan dalam Rangka Diversifikasi Produk Kopi - Wiratama, I Gusti Ngurah Made; Wijaya, I Made Wahyu; Paramitha, Anak Agung Istri Ita (Jurnal SOLMA, 2024)
Background: This Community Partnership Program (PKM) focuses on empowering coffee farmers in Pujungan Village, Pupuan District, Tabanan Regency, by converting coffee husk waste into value-added products such as compost, mushroom growing media (baglog), and coffee soap. Coffee production generates significant waste, especially coffee husks, which account for 50-60% of the total production. If not properly managed, this waste can pose environmental risks such as soil and water pollution, as well as greenhouse gas emissions. The goal of the program is to reduce coffee waste volume while creating new, waste-based products. Method: Farmers' ability to independently manage coffee waste is enhanced through structured and practical training. Through this PKM, the Kelompok Petani Cipta Lestari coffee farmers were trained and mentored to improve their skills in processing coffee husks. Results: The program includes training on composting, mushroom baglog production, and coffee soap making. The PKM in Pujungan Village successfully transformed coffee husk waste into compost, mushroom baglog, and coffee soap, increasing farmers' income by 20-30% and reducing waste by 60-70%. Conclusion: This program also positively impacted soil quality and the environment, while providing farmers with new skills for sustainable product diversification.